OPTIMISING THE QUALITY OF GRADUATES TROUGH THE DEVELOPMENT OF CHARACTER AND COMPETENCE OF ULUMUDDIN VOCATIONAL HIGH SCHOOL - Jumira, Jumira; Prasetyo, Muhammad Anggung (PASCASARJANA UNISNU, 2025)
This study aims to identify school policies, strategies and practices in developing students' character and competencies in the 21st century learning era, especially at the level of Ulumuddin Vocational High School (SMK). The research approach used a descriptive qualitative method with in-depth interviews with the principal, subject teachers, support staff, and the accreditation team. Data were collected through observation and semi-structured interviews and then analyzed using triangulation techniques. The results showed that student character development is carried out through consistent discipline policies, integrated religious programs, and regular evaluations based on character assessment rubrics. In student competencies, the school applies collaborative strategies to develop communication skills, critical thinking, and creativity through project-based approaches and partnerships with the business world. The accreditation team relies on achievement data, competency certificates and activity reports as supporting evidence of student quality achievement. The implications of this study show the importance of synergy between school policies, teacher mentoring and collaboration with external parties to create a learning environment that is adaptive to the challenges of 21st century education. The findings can serve as a reference for policy makers and education practitioners in improving the quality of graduates with character and competence.